ナンキョク イキ ニ オケル ブーゲー イジョウ ブンプ ト ソレ ニ モトヅク チカ コウゾウ - 松本, 剛; マツモト, タケシ; 瀬川, 爾朗; セガワ, ジロウ; 神沼, 克伊; カミヌマ, カツタダ; Matsumoto, Takeshi; Segawa, Jiro; Kaminuma, Katsutada (1986)
P(論文) 南緯45度以南の南極域のフリーエア異常および地形の最新のデータを用いてブーゲー異常分布を求め, 大陸域およびそれと隣接する海域の地下構造に関して重力異常の立場から考察を行った。大陸域は全体が負の異常を示す。これは厚い氷床と基盤地形との荷重を厚い地殻がアイソスタティックに支えていることを示している。大陸の周辺部の海域には, 大洋中央海嶺に対応して, 周囲に比べて相対的に負の異常を示す地帯が存在する。また, さらに詳しい解析を行った結果, ロス海の地下構造は中央海嶺と関連性があり, しかもこの地域ではリソスフェアとアセノスフェア境界面が明瞭でなく, アセノスフェアが地殻下面まで達していることを示唆する結果が得られた。 Bouguer gravity anomaly south of 45°S was derived from the newly provided data of free-air anomaly and topography, and its implications in the crust and upper mantle structure of the land and its marginal ocean area were discussed from the viewpoint of gravity anomaly. Bouguer anomaly in the Antarctic Continent presents negative anomaly, showing that the land area is in isostatic equilibrium with the thick crust supporting the load of both thick ice sheet and bedrock topography. In the surrounding ocean area exists the zone of relatively negative anomaly corresponding to the mid-oceanic ridges. The result of further analysis shows that there is some relationship between the sub-bottom structure of the Ross Sea and that of mid-oceanic ridges, and that no clear boundary of lithosphere and asthenosphere is recognized, which suggests that the asthenosphere reaches up to the bottom of the crust in this place. departmental bulletin paper